Mothers as “Others”: Identity of Mothers of Children with Disabilities and Adult Education Discourse - Tulare W Park; Carol Rogers-Shaw (Adult Education Research Conference, 2018)
This literature review will explore experiences and identity development of mothers of children with disabilities. Intersections between adult education and critical disability theory, as well as practice implications, are identified.
Keywords: disability; identity; adult education discourse; critical disability theory; social justice